2014
DOI: 10.1523/jneurosci.4767-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Training Improves Auditory Spatial Processing following Bilateral Cochlear Implantation

Abstract: Cochlear implants (CIs) partially restore hearing to the deaf by directly stimulating the inner ear. In individuals fitted with CIs, lack of auditory experience due to loss of hearing before language acquisition can adversely impact outcomes. For example, adults with earlyonset hearing loss generally do not integrate inputs from both ears effectively when fitted with bilateral CIs (BiCIs). Here, we used an animal model to investigate the effects of long-term deafness on auditory localization with BiCIs and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 78 publications
(41 reference statements)
3
56
1
Order By: Relevance
“…Such supramodal linguistic networks may be increasingly activated by both audition and vision, as an individual CI patient learns to optimally integrate auditory and visual information to maximize language understanding. In an animal model, vision has been shown to play a facilitative role in restoring sound localization abilities after cochlear implantation (28). In parallel, our findings provide unique evidence in humans for a synergistic relationship between audition and vision within auditory brain regions, indicating a facilitative mechanism between the modalities that underlies the restoration of speech understanding following cochlear implantation.…”
Section: Discussionsupporting
confidence: 61%
“…Such supramodal linguistic networks may be increasingly activated by both audition and vision, as an individual CI patient learns to optimally integrate auditory and visual information to maximize language understanding. In an animal model, vision has been shown to play a facilitative role in restoring sound localization abilities after cochlear implantation (28). In parallel, our findings provide unique evidence in humans for a synergistic relationship between audition and vision within auditory brain regions, indicating a facilitative mechanism between the modalities that underlies the restoration of speech understanding following cochlear implantation.…”
Section: Discussionsupporting
confidence: 61%
“…Unlike Loizou et al who used speech maskers, Eapen et al used noise maskers like van Hoesel et al A binaural-interaction benefit was evidenced by improved performance when the worse ear – i.e., the CI on the side of the head closest to the noise – was added to the better ear. The fact that this benefit emerged after more than a year of listening experience raises the possibility that binaural advantages may emerge or increase with long-term BI-CI or SSD-CI listening experience or training (e.g., Tyler et al 2010; Isaiah et al 2014; Reeder et al 2015). The current study demonstrated that a binaural-interaction benefit was much more easily observed for a situation involving the perceptual separation of interfering talkers than for a noise interferer.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrets have been used extensively in physiological and anatomical studies of multisensory processing (e.g. King & Hutchings, 1987;King et al, 1988;King & Schnupp, 2000;Bizley et al, 2007;Bizley & King, 2008;Stitt et al, 2015), but only to a limited degree so far in behavioural experiments (Isaiah et al, 2014;Hollensteiner et al, 2015), despite the ease with which they can be trained to carry out localization and other sensory tasks. We have previously characterized sound localization behaviour in this species by measuring their head-orienting response following stimulus presentation and the subsequent locomotor response as the animals approach the perceived location of the sound source to receive a water reward (Nodal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%